On the Existence of a Middle‐Income Trap1. Issue 297 (4th March 2016) - Ye, Longfeng; Robertson, Peter E.
Abstract : The concept of a 'middle‐income trap' has attracted enormous interest, but the existing literature lacks formal tests. We develop and apply a test of some necessary conditions for a country to be in a middle‐income trap that take into account short‐run dynamics, stochastic trends and structural breaks. We find that only seven countries satisfy our definition of a middle income trap.